KEPUTUSAN PEMBELIAN : KUALITAS PELAYANAN DAN HARGA DI Bendang Minimarket LIMA KAUM, BATUSANGKAR - Khairulis Shobirin; Mirawati Mirawati; Nita Fitria; Atika Hariani (IAIN Batusangkar, 2020)
The purpose of this study was to find out the influence of services quality and prices toward purchasing decisions at Bendang Minimarket, Lima Kaum, Batusangkar. This type of research was field research with descriptive methods. The results showed (1) there is a positive and significance influence of service qualities on purchasing decisions, (2) there is no influence of prices on purchasing decisions, and (3) both service qualities and prices have positive influence (70,9%) on purchasing decisions at Bendang Minimarket. While other factors (29,1%) also influence purchasing decisions.